Dinamika Kualitas Audit Di Perbankan Syariah Di Indonesia - Riani Riani; Sepky Mardian (Jurnal Akuntansi dan Keuangan Islam, 2017)
This study discusses and understands the competence and independence of auditors on audit quality in sharia banking in Indonesia. While in the discussion the authors analyze the things that are deemed related to the competence and independent audit of auditor tenure or rotation seen through two post-KMK regime and post Act No. 5, Audit firm reputation by looking at audit firm size, audit fees, and auditor competencies determined through background education, certification, experience of work, and frequency of training that followed. The result of the research shows that the limitation of audit tenure does not decrease the quality of audit in sharia banking, the dynamics of audit quality is formed from independent relationship and auditor competence depends on the maximum level of audit